2016
DOI: 10.12659/msm.901467
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Polymorphism (-174, G/C) of Interleukin-6 and Arterial Thromboembolic Events: A Meta-Analysis

Abstract: BackgroundIschemic stroke and myocardial infarction are fatal diseases and are among the top 10 causes of death in Korea, including arterial thromboembolic events. Many previous studies have described the function of interleukin-6 (IL-6) in arterial thromboembolic events and the association between promoter single-nucleotide polymorphism (SNP) (rs1800795; −174, G/C) of the IL-6 gene. However, these results were controversial. Therefore, we performed a meta-analysis to more precisely assess the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…However, there are unequivocal opinions regarding the role of this polymorphism with thrombosis. Our results are in line with two previous studies where they have reported no association of this polymorphism with the risk of ischemic stroke in South Korean and DVT in European population, respectively [6,18]. In contrary to these findings, one recent study suggested marginal association of −174 G > C polymorphism with thrombotic risk in venous and arterial thrombotic disorders in Asian population [19].…”
Section: Discussionsupporting
confidence: 90%
“…However, there are unequivocal opinions regarding the role of this polymorphism with thrombosis. Our results are in line with two previous studies where they have reported no association of this polymorphism with the risk of ischemic stroke in South Korean and DVT in European population, respectively [6,18]. In contrary to these findings, one recent study suggested marginal association of −174 G > C polymorphism with thrombotic risk in venous and arterial thrombotic disorders in Asian population [19].…”
Section: Discussionsupporting
confidence: 90%
“…Odds ratios (OR) and 95% confidence intervals (CI) were calculated for effect of genotypes and allele frequencies at the 5% level of significance. For the logistic regression analysis of genetic data, SNPStats and SPSS 17.0 were used [ 20 ]. Logistic regression analysis was performed to investigate the association between SNPs of the IL-1 family of genes and HCC adjusted by age and sex.…”
Section: Methodsmentioning
confidence: 99%
“…Logistic regression analysis was performed to investigate the association between SNPs of the IL-1 family of genes and HCC adjusted by age and sex. A linkage disequilibrium (LD) block of polymorphisms was analyzed using Haploview 3.32 [ 20 , 21 ]. The haplotypes and their frequencies were calculated using the EM algorithm.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported that IL-6 -174 polymorphism has been associated with CAD [18,19], type II diabetes mellitus [17]. In a meta-analysis, reported the significant association between the incidence of stroke and IL-6 -174G/C polymorphism [20,21].…”
Section: Introductionmentioning
confidence: 99%